Copper(II)-Catalyzed Chemo- and Stereocontrolled Synthesis of (E)-Vinyl Sulfones and (Z)-β-Chlorovinyl Sulfones from Terminal Alkynes and Arylsulfonyl Hydrazides - Liu, Xiao-Tao; Ding, Zong-Cang; Ju, Lu-Chuan; Xu, Su-Xia; Zhan, Zhuang-Ping (Synthesis, 2017)
A facile copper(II)-catalyzed regio- and stereocontrolled synthesis of vinyl sulfones from terminal alkynes and arylsulfonyl hydrazides is described. Depending on the source of copper(II), two different kinds of vinyl sulfones, (E)-vinyl sulfones and (Z)-β-chlorovinyl sulfones were obtained and the addition of cyclohexanone played an important role in the reaction. These reactions display excellent chemoselectivity as well as stereoselectivity.
Keywords: copper(II); catalysis; vinyl sulfones; terminal alkynes; arylsulfonyl hydrazides; cyclohexanone; chemoselectivity; stereoselectivity